COVID-19 Vaccine Hesitancy, Delays and Barriers among Educated Middle-class of Population in Delhi, NCR Region, India - Ananya Ray Laskar; Shyambhavee Behera; Aditi S. Poddar; S. K. Rasania; S. S. Saha (Current Overview on Disease and Health Vol. 7, 2023)
Introduction: Vaccine hesitancy or delay during any novel pandemic may pose a serious threat to its control. In India COVID-19 vaccines were introduced in a phased manner initially for health care workers (Jan 2021) closely followed by \(\) 60years and then \(\)45 years, subsequently for all the adults by May 2021. Exploring the reasons of hesitation or delay and assessing the barriers in vaccination Objectives: i) To estimate the vaccine hesitancy or delay in COVID-19 vaccination among school teachers, their family members and close relatives. ii) To determine the reasons& barriers leading to hesitancy/delay. iii) To access their opinion regarding vaccination of children, pregnant and lactating mothers. Methods: An online cross-sectional follow-up study was conducted among teachers and their eligible family members, using semi-structured questionnaire on vaccination status, reasons or barriers for hesitancy/delay and opinion regarding vaccinating children, pregnant women incorporated into kobo toolbox. A follow up study was undertaken in August 2022 in the same group to access the uptake of booster dose. The determinants to hesitancy were assessed and data was analysed using SPSS version 20. Results: Out of total 362 participants, 43% were totally unvaccinated. Most common reasons included doubts regarding vaccine effectiveness (52.3%) and apprehension about the side effects (48.6%). The sources that influenced their opinion were Whats app and other social media (39%) rather than credible sources. 35% opined that the vaccines may be harmful if given to special groups such as children and pregnant women. Conclusion: Risk communication and vaccine advocacy should be tailor-made to curb all doubts among general public and counter the misinformation in order to improve the vaccine uptake.